Towards Sustainable Development of Islamic Higher Education: A Meta-Analysis of Challenges and Opportunities - Desmaniar; Rusli; Aqil Teguh Fathani; Novia Amirah Azmi; Muhammad Mughni; Imam Rasikh Islami; Abdan Syukri (Millah: Journal of Religious Studies, 2022)
This paper aims to describe the challenges and opportunities in the growth of sustainable development of Islamic higher education in Indonesia to construct an effective management system in terms of both quality and quantity. Such a system should enable us to evaluate the effectiveness of Islamic education in combating radicalization, terrorism, and sexual harassment, as well as promoting efforts to expand human resources. The Scopus database was searched for articles on "Higher Education" AND "Management" AND "Islam" OR "Muslim," yielding 141 papers pertinent to the main research topic. In Islamic higher education, the governance structure, structuralization, human resource capabilities, learning methods, curriculum, and knowledge of technology continue to lag behind those of conventional higher education. Lack of domestic and international cross-sectoral collaboration activities has become a significant barrier to improving Islamic higher education quality. Due to the study's limitations, a more precise measurement with a narrower scope is required to analyze the governance of the Islamic higher education system across regions to produce conclusions that can speed up governance changes. Furthermore, comparative research between two or more countries is required in future research so that particular answers to the issues of Islamic higher education in Indonesia may be established directly.